Rare Taxa Drive the Response of Soil Fungal Guilds to Soil Salinization in the Taklamakan Desert - Lin, Litao; Jing, Xin; Lucas-Borja, Manuel Esteban; Shen, Congcong; Wang, Yugang; Feng, Wenting (Frontiers in Microbiology, 2022)
Salinization poses great threats to soil fungal communities that would cause the losses of ecosystems services. Soil fungal communities are composed of different functional guilds such as saprotrophic, symbiotrophic, and pathotrophic fungi, and each guild includes many rare taxa and a few abundant taxa. Despite of low abundance, rare taxa may be crucial in determining the responses of entire soil fungal communities to salinization. However, it remains poorly understood how rare taxa mediate the impacts of soil salinization on soil fungal community structure. Here, we took advantage of a salinity gradient in a desert ecosystem ranging from 0.60 to 31.09 g kg-1 that was created by a 12-year saline-water irrigation and assessed how the rare vs. abundant taxa of soil saprotrophic, symbiotrophic, and pathotrophic fungi respond to soil salinization through changes in the community biodiversity and composition. We found that the rare taxa of soil saprotrophic, symbiotrophic, and pathographic fungi were more sensitive to changes in soil salinity compared to the abundant taxa. In addition, the community composition of rare taxa of the saprotrophic and pathotrophic fungi not the symbiotrophic fungi was positively associated with soil salinity change. However, the symbiotrophic fungi showed greater variations in the species richness of fungal taxa along the salinity gradient. These findings highlight the importance to differentiate rare taxa in predicting how the biodiversity and functional groups of soil fungal communities respond to soil salinization.